(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The research aims to determine the initial process of dam construction is seen from a topographical perspective ( bench mark coordinate and control point coordinates: case study of D.I. Bajayu kab. Serdang Bedagai. The aim and objective of this topographic survey is to collect topographical data from the field in order to produce supporting data in the form of a topographical/situation base map including cross-sectional and longitudinal cross sectional images along the measurement location. Measurement 20 data of topographi for BM coordinat and CP coordinat, so: measurements are made up to 50 meters from the left and right bank of the river, measurement lengthwise (long section) of ± 8.2 km was carried out from the confluence of the Padang river with the Bah disappeared river to the Bajayu free intake location, measurement benchmark interval for 100 meters straight area and 50 meters turning area,conduct measurements on the linking route/trace from the planned main building to the free intake of D.I Bajayu and the first building for D.I Paya Lombang, measuring 50 meter intervals, the length of the measurement path from the axle of the weir to the Bajayu free intake is 3,600 m following the embankment to the right of the Padang river, the length of the canal trace from the axle of the weir to the building for the first Paya Lombang is 4,600 m following the existing road.